2021
DOI: 10.1017/s095026882100090x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling designs for rare time-dependent exposures: a comparison of the nested exposure case-control design and exposure density sampling

Abstract: In extensive cohort studies, the ascertainment of covariate information on all individuals can be challenging. In hospital epidemiology, an additional issue is often the time-dependency of the exposure of interest. We revisit and compare two sampling designs constructed for rare time-dependent exposures and possibly common outcomes – the nested exposure case-control design and exposure density sampling. Both designs enable efficient hazard ratio estimation by sampling all exposed individuals but only a small f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For example, one could investigate the different effect of a covariate on discharge alive compared to death, which we combined due to simplicity. When interested in the consequences of infection, rather than the risk of infection, the analysis can be expanded for all three study designs as shown nicely by von Cube et al 18 for the case-cohort design, by Feifel et al 28 for the nested-case cohort design and by Doerken et al 23 for the point-prevalence design.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one could investigate the different effect of a covariate on discharge alive compared to death, which we combined due to simplicity. When interested in the consequences of infection, rather than the risk of infection, the analysis can be expanded for all three study designs as shown nicely by von Cube et al 18 for the case-cohort design, by Feifel et al 28 for the nested-case cohort design and by Doerken et al 23 for the point-prevalence design.…”
Section: Discussionmentioning
confidence: 99%